Stability of ultra-high pressure treated freshly squeezed Hami melon juice under simulated commercial cold chain conditions - Jinxiao Cheng; Congcong Huai; Di Shen; Yining Xia; Yang Yang; Yifan Gu; Jiakai Yu; Lingling Pang; Jia Liu; Yanfang Pan (Food Control, 2026)

Enhanced emulsification via pH-dependent complexation: Structural and interfacial engineering of hempseed protein hydrolysates by anionic polysaccharides - Qingling Wang; Xi Sun; Yu Qian; Yining Feng; Yanyun Cao; Mangang Wu; Tuanzhu Guan; Hai Yu (Journal of Food Engineering, 2026)

Morphology-based ovarian stratification reflects coordinated redox imbalance and apoptosis across ovarian tissue, follicular fluid, and granulosa cells in cattle - Jiatong Yu; Fanqi Zhao; Yining Zhu; Zhongrui Zang; Dianrui Xu; Dayi Liu; Yuxuan Lu; Qingshan Gao (Theriogenology, 2026)

Effect of liquefaction solvent, catalyst sulfidation method and H2S on mild liquefaction behaviors of Jiangna coal over Fe-based catalysts - Jiaqi Yu; Yuxin Wen; Shuo Wang; Rui Zhang; He Yang; Yang Li; Xingxing Xiao; Yining Guan; Haoquan Hu; Lijun Jin (Fuel, 2026)

Construction of oregano essential oil Pickering emulsions stabilized by Nanocellulose from Xanthoceras sorbifolium shell: Unraveling antibacterial and antioxidant synergy for Agaricus bisporus preservation - Jiayi Du; Yu Huang; Meixi Zhong; Dongmei Li; Yining Chen; Yuanyu Li; Weixia Yang; Long Chen; Xiaoxiao Feng; Yuan Liu; Haiwei Ren (Food Chemistry, 2026)

Retraction notice to “Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period” [Sci. Total Environ. 906 (2024) 167622] - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2026)

Second-scale synthesis of oxygen-doped carbon nanotubes for oxygen reduction to hydrogen peroxide and valorization - Yining Sun; Jinze Li; Yu Fu; Zhenhua Li; Mingfei Shao (Science Bulletin, 2026)

Optimization of combined heat source parameters and robust interval determination of welding process parameters for deep-sea riser welding - Jianxing Yu; Yining Jin; Hanjun Yin; Ruoke Sun; Zihang Jin; Mingkun Cai; Qingming Zou (Ocean Engineering, 2026)

Evaluation of 2-m Air Temperature and Surface Temperature from CMA-RA and ERA5: A Comparison with Buoy Observations in the Arctic during 2001–2024 - Yue Cui; Yining Yu; Jiechen Zhao; Xueqin Liu; Jiajia Jia; Xiaowei Zou; Biao Tian; Minghu Ding (Journal of Meteorological Research, 2026)

Development and immunoprotective evaluation of a chitosan-based nanovaccine against Aeromonas hydrophila in Yangtze sturgeon (Acipenser dabryanus) - Yining Chen; Ying Qin; Jiachen Zhou; Ye Zhang; Chenwei Yu; Yacheng Hu; Yuanjin Yang; Dan Xu (Fish & Shellfish Immunology, 2026)

Solvent-engineering enabled high-performance large-area red perovskite light-emitting diodes - Haoyan Wang; Fujun Zhang; Yongqi Liu; Siyu Zhang; Xinhao Guo; Hengjia Liu; Yining Chen; Weinan Dong; Kang Liu; Feng Jiang; Min Lu; Chunru Fan; et al. (Chemical Engineering Journal, 2026)

The long non-coding RNA PVT1 promotes keratinocyte proliferation and inflammation in psoriasis by targeting miR-485-5p - Wanwan Yu; Boling Qi; Can Cong; Yining Ma; Qingtao Kong; Hong Sang (Journal of Molecular Histology, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Single-nucleus RNA sequencing reveals adipocyte lineage relationships and differentiation trajectory between intramuscular and intermuscular fat tissues of rainbow trout - Ming Huang; Xiangbing Zeng; Yuan Yao; Jinghong He; Wenxin Jiang; Yining Yu; Qingkai Tang; Qinfeng Gao; Yuan Tian (Aquaculture, 2026)

Metal-polyphenol network-mediated walnut protein complexes alleviate food allergy via gut microbiota and metabolic modulation - Zining Luo; Jian Yu; Zhen Liu; Xiaolin Zhang; Yining Jia; Wei Cao; Fangyu Long (Food Bioscience, 2026)

Nighttime Encounter Situation Recognition for Unmanned Surface Vessels Based on Images of Vessel Navigation Lights - Ruoyun Huang; Xiang Zheng; Jianhua Wang; Gongxing Wu; Yu Tian; Yining Tian (Journal of Marine Science and Engineering, 2026)
To address the limitations of existing perception methods for nighttime encounter situation recognition of unmanned surface vessels (USVs), this study proposes an image-based method for navigation-light recognition and encounter situation recognition. In accordance with the International Regulations for Preventing Collisions at Sea (COLREGs), a parameterized 3D geometric model of vessel navigation lights and encounter scenario models is established. Based on the camera imaging principle, a dataset of navigation-light images under various encounter situations is generated through simulation experiments. By analyzing the variation patterns of navigation-light images in different encounter situations, a feature vector composed of area-domain and azimuth-domain features is constructed, and an encounter situation recognition method is developed accordingly. To mitigate the effects of water reflections and interfering light sources in real images, a navigation-light image-processing method is designed for the stable extraction of feature parameters. Simulation results show that the classification accuracy ranges from 96.6% to 98.3% at different distance conditions. In field experiments conducted with a small USV under a three-light configuration, the proposed method achieves a navigation-light recognition accuracy of 96.2% and an encounter situation recognition accuracy of 94.94%. The proposed method provides an interpretable and lightweight complementary visual solution for nighttime encounter situation recognition, complementing existing nighttime perception technologies.

Nonlinear control of offshore cranes for underwater payload transportation under wave-induced ship motions with full-state constraints - Ling Yang; Xin Ma; Guodong Jiang; Huanqi Yang; Yining Yu (Ocean Engineering, 2026)

MoS2@Fe3O4 nanozyme redirects carbon to strengthen symbiotic nitrogen fixation in soybean for fertilizer-minimizing cleaner production - Kan Huang; Yining Liu; Youyou Zhao; Qingyun Xu; Chengxiao Hu; Qiling Tan; Songwei Wu; Sergey Shabala; Min Yu; Xuecheng Sun (Journal of Cleaner Production, 2026)

Comparative study of promising CaAl-LDH and conventional immobilizing agents in mitigating ecological and health risks associated with soil Pb contamination - Jianying Yu; Nan Wei; Haochen Fang; Yining Chen; Tengfei Guo; Qijia Zhang; Yangyang Chen; Jiahong Yu; Jianyu Zhang; Zeliang Han; Kaiqin Xu; Ching Yuan; et al. (Journal of Environmental Management, 2026)

Review: Synergistic effects of environmental pollutants: Multiple stressors driving the transmission of vector-borne diseases and the vicious cycle - Tingting Liu; Jia Wang; Minghao Yu; Yining Li; Huan Lin; Dan Deng; Xiaolu Shi; Xiaoping Xiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Propagation characteristics of projected meteorological to hydrological droughts in the Poyang Lake Basin - Yining Xie; Yanzhong Li; Dan Zhang; Wenjun Yu; Haiwen Yan; Huan Wu (Theoretical and Applied Climatology, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Novel Z-scheme BiOBr/CoWO4 heterojunction for efficient photocatalytic degradation of tetracycline: Mechanistic insight and toxicity assessment - Yining Hu; Yiming Yu; Yangyang Zhang; Yuqi Wu; Yanhao Zhang; Zifang Peng; Congcong Pei; Wenfen Zhang; Dan Yin; Shusheng Zhang (Journal of Water Process Engineering, 2025)

Photo-enzyme synergistic catalysis by nitrogen-doped titanate nanotubes for efficient microplastic degradation: Acceleration of Ti valence cycle under visible light irradiation - Li Kang; Yining Xing; Haibo Yu; Jing Lu (Journal of Environmental Chemical Engineering, 2025)

Preparation of sodium alginate/sodium carboxymethyl cellulose composite coating film and evaluation of its effects on mango preservation - Wei Wang; Jiakai Yu; Yuting Huang; Bai-Jun Li; Wenzhu Shen; Wenli Zhang; Yining Xia; Qiong Lin (Food Chemistry, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Flooding-drainage regulates arsenic transformation and its associated microbial dynamics in paddy soil amended with ferrihydrite - Shaopeng Jia; Jianbo Chen; Yujuan Fang; Xiu Yi; Manjia Chen; Yining Gao; Huanyun Yu; Chengshuai Liu; Hui Tong (Journal of Soils and Sediments, 2025)

Chemical constituents and bioactivities of fermented rose (from Yunnan ) extract - Bo Peng; Yining Hao; Yueyue Chen; Shishuai Yu; Liping Qu (Natural Product Research, 2025)

Novel insight into the heavy metal immobilization by coal fly ash-based geopolymers using machine learning and density functional theory - Kaizhi Yang; Bo Yang; Kezhou Yan; Yining Su; Longyi Zhao; Jungang Tang; Yu Che; Yanxia Guo (Waste Management, 2025)

Phosphorus-doped BiOBr nanoflowers with oxygen vacancy for photocatalytic degradation of ofloxacin: Mechanism insight and toxicity assessment - Dan Yin; Yiming Yu; Yangyang Zhang; Yining Hu; Congcong Pei; Wenfen Zhang; Wuduo Zhao; Yanhao Zhang; Shusheng Zhang; Xiaoquan Lu (Journal of Environmental Chemical Engineering, 2025)

Nature-inspired catechol-silicon complexation for robust superspreading and efficient crude oil recovery in high-salinity environments - Jianning Yu; Xiaotao Yang; Peijia Li; Enfeng Yang; Haitao Deng; Guoliang Liu; Xiangdong Yang; Shende Zhai; Lu Zhang; Yining Wu; Dezhao Hao; Caili Dai; et al. (Chemical Engineering Journal, 2025)

Millimeter-scale leaf litter placement modulates carbon dioxide and methane emissions in wetlands - Hao Liu; Yining Zhang; Yu-Jia Cai; Zi-Yan Liu; Liang Li; Ya-Qin Wang; Xiao Shu; Royston Goodacre; Zheng Chen (Applied Geochemistry, 2025)

Integrating computer vision and machine learning technologies for model building to quantify intermuscular fat content in salmonid fillets - Ming Huang; Libo Wang; Boyuan Wang; Wenxin Jiang; Yining Yu; Qingkai Tang; Qinfeng Gao; Yuan Tian (Food Control, 2025)

Construction of a “rigid-flexible” double-locking transition layer based on “mortar-brick–mortar” structure to achieve the effective transfer of stress at the interface - Zhiqiang Yao; Anqi Xia; Yining Wang; Kaining Zhang; Lilin Yang; Mingdong Yu; Dongzhi Wang (Chemical Engineering Journal, 2025)

Double-punch strategy: Macrophage membrane-enveloped imipramine and aCD47 reprograms tumor microenvironment to enhance glioblastoma immunotherapy - Long Zhang; Yining Zhang; Ji Qi; Jiahao Yu; Haojie Hu; Xiangrong Lu; Jiangpeng Fan; Guimei Cui; Rutong Yu; Xiuping Zhou (Chemical Engineering Journal, 2025)

Dose-dependent inflammatory and neurotoxic effects of polypropylene microplastics in Nile tilapia evidenced by internal extractive electrospray ionization high-resolution mass spectrometry metabolomics - Xiaokang Wu; Susu Pan; Ming Li; Jiaxin Dong; Yining Wang; Chenni Huang; Tao Qiu; Yu Gu; Dapeng Liang (Environmental Chemistry Letters, 2025)

Dissolved oxygen prediction in the Dianchi River basin with explainable artificial intelligence based on physical prior knowledge - Junhao Wu; Xi Chen; Jinghan Dong; Nen Tan; Xiaoping Liu; Antonis Chatzipavlis; Philip LH. Yu; Adonis Velegrakis; Yining Wang; Yonggui Huang; Heqin Cheng; Diankai Wang (Environmental Modelling & Software, 2025)

Connexin43 Contributes to Alzheimer’s Disease by Promoting the Mitochondria-Associated Membrane-Related Autophagy Inhibition - Weiwei Yu; Yunong Li; Yao Li; Jun Hu; Jun Wu; Xuhui Chen; Yining Huang; Xin Shi (Molecular Neurobiology, 2025)

Landscapes of alternative splicing genes/events in the gills of Mozambique tilapia (Oreochromis mossambicus) and their roles in high-salinity adaptation - Ming Huang; Han Yu; Boyuan Wang; Wenxin Jiang; Na Xue; Hancheng Bao; Yining Yu; Qingkai Tang; Qinfeng Gao; Yuan Tian (Aquaculture International, 2025)

Exploring the immunomodulatory mechanisms of Osmunda japonica Thunb polysaccharides: Activation of MAPK and NF-κB signaling pathways - Xiaochen Liu; Rui Xu; Yuting Miao; Yining Zang; Yuxin Huang; Yuying Zheng; Fengwei Li; Ming Wei; Rui Xiao; Xiaohong Yu (Food Bioscience, 2025)

Combined dynamic transcriptome and flavonoid metabolome reveal the role of Mo nanoparticles in the nodulation process in soybean - Yining Liu; Songwei Wu; Xiaoming Qin; Min Yu; Sergey Shabala; Xiaomei Zheng; Chengxiao Hu; Qiling Tan; Shoujun Xu; Xuecheng Sun (Science of The Total Environment, 2024)

Modularization of dual recognized CRISPR/Cas12a system for the detection of Staphylococcus aureus assisted by hydrazone chemistry - Jingyi Yang; Yining Zhao; Lelin Qian; Ying Yu; Yuan Zhang; Juan Zhang (Journal of Hazardous Materials, 2024)

Effect of plasma on ochratoxin degradation and raisin properties - Ying Wang; Yu Zheng; Jianjun Wang; Longtao Mu; Wenting Zhang; Mengting Huang; Yining Li (Journal of Food Engineering, 2024)

External carbon source as a viable tool for controlling antibiotics and antibiotic resistance genes (ARGs) in effluent: Influence on antibiotic removal and ARGs dissemination - Yining Qu; Peng Li; Yuxue Liu; Sha Dai; Yu Xie; Yiliang He (Journal of Environmental Management, 2024)

Unlocking the concentration polarization for Solid-State lithium metal batteries - Jiameng Yu; Yining Zhang; Tianyi Gao; Xinshui Zhang; Yinjie Lv; Yue Zhang; Chang Zhang; Wei Liu (Chemical Engineering Journal, 2024)

Filtration of polystyrene nanoplastics with different functional groups by natural mineral materials: Performance and mechanisms - Hao Wang; Yu Wang; Tongyu Zhang; Yining Ji; Yuanyuan Zhang; Yufei Wang; Xiaohui Li (Marine Pollution Bulletin, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Non-targeted metabolomics provides insights into the distinct amino acid and lipid metabolism in liver tissues of rainbow trout (Oncorhynchus mykiss) cultured in seawater at different temperatures - Yuan Tian; Wen Wang; Wenxin Jiang; Gong Zhang; Jinghong He; Shuanglin Dong; Yangen Zhou; Wenzhao Yang; Qingkai Tang; Yining Yu; Qinfeng Gao (Aquaculture, 2024)

RETRACTED: Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2024)

Effects of bubble and reactor shape on cold plasma yeast inactivation - Ying Wang; Guanting Pan; Yining Li; Longtao Mu; Mingwei Zhao; Yu Zheng (Journal of Food Engineering, 2024)

Individual and combined effects of phthalate metabolites on eczema in the United States population - Xiaoqian Li; Na Zheng; Yan Yu; Wenhui Zhang; Siyu Sun; Qirui An; Zimeng Li; Yining Ji; Sujing Wang; Ying Shi; Wanlei Li (Environmental Research, 2024)

Enhancing Zn2+ diffusion for dendrite-free zinc anodes via a robust zincophilic clay mineral coating - Mengjiao Liu; Anjun Hu; Zhongfu Yan; Jiahao Chen; Miao He; Bo Zhou; Yu Pan; Yining Fan; Daojiang Gao; Jianping Long (Chemical Engineering Journal, 2024)

The neglected roles of adjacent natural ecosystems in maintaining bacterial diversity in agroecosystems - Ziheng Peng; Yunfeng Yang; Yu Liu; Lianyan Bu; Jiejun Qi; Hang Gao; Shi Chen; Haibo Pan; Beibei Chen; Chunling Liang; Xiaomeng Li; Yining An; et al. (Global Change Biology, 2024)
A central aim of community ecology is to understand how local species diversity is shaped. Agricultural activities are reshaping and filtering soil biodiversity and communities; however, ecological processes that structure agricultural communities have often overlooked the role of the regional species pool, mainly owing to the lack of large datasets across several regions. Here, we conducted a soil survey of 941 plots of agricultural and adjacent natural ecosystems (e.g., forest, wetland, grassland, and desert) in 38 regions across diverse climatic and soil gradients to evaluate whether the regional species pool of soil microbes from adjacent natural ecosystems is important in shaping agricultural soil microbial diversity and completeness. Using a framework of multiscales community assembly, we revealed that the regional species pool was an important predictor of agricultural bacterial diversity and explained a unique variation that cannot be predicted by historical legacy, large‐scale environmental factors, and local community assembly processes. Moreover, the species pool effects were associated with microbial dormancy potential, where taxa with higher dormancy potential exhibited stronger species pool effects. Bacterial diversity in regions with higher agricultural intensity was more influenced by species pool effects than that in regions with low intensity, indicating that the maintenance of agricultural biodiversity in high‐intensity regions strongly depends on species present in the surrounding landscape. Models for community completeness indicated the positive effect of regional species pool, further implying the community unsaturation and increased potential in bacterial diversity of agricultural ecosystems. Overall, our study reveals the indubitable role of regional species pool from adjacent natural ecosystems in predicting bacterial diversity, which has useful implication for biodiversity management and conservation in agricultural systems.

Ubiquitin-specific peptidase 47 (USP47) regulates cutaneous oxidative injury through nicotinamide nucleotide transhydrogenase (NNT) - Xiaoqian Li; Kun Qian; Yuehua Zhang; Yining Zhang; Yulan Liu; Chuntang Sun; Yang Jiao; Daojiang Yu; Fenghao Geng; Jianping Cao; Shuyu Zhang (Toxicology and Applied Pharmacology, 2023)

Free amino acids in response to salinity changes in fishes: relationships to osmoregulation - Ming Huang; Qinfeng Gao; Xiaogang Yang; Wenxin Jiang; Lin Hao; Yining Yu; Yuan Tian (Fish Physiology and Biochemistry, 2023)

Estimating wheat grain yield by assimilating phenology and LAI with the WheatGrow model based on theoretical uncertainty of remotely sensed observation - Yining Tang; Ruiheng Zhou; Ping He; Minglei Yu; Hengbiao Zheng; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Agricultural and Forest Meteorology, 2023)

A safe anode-free lithium metal pouch cell enabled by integrating stable quasi-solid electrolytes with oxygen-free cathodes - Chuan Zhao; Yu Pan; Runjing Li; Anjun Hu; Bo Zhou; Miao He; Jiahao Chen; Zhongfu Yan; Yining Fan; Nian Chen; Mengjiao Liu; Jianping Long (Chemical Engineering Journal, 2023)

Application of Deep Learning-Based Object Detection Techniques in Fish Aquaculture: A Review - Hanchi Liu; Xin Ma; Yining Yu; Liang Wang; Lin Hao (Journal of Marine Science and Engineering, 2023)
Automated monitoring and analysis of fish’s growth status and behaviors can help scientific aquaculture management and reduce severe losses due to diseases or overfeeding. With developments in machine vision and deep learning (DL) techniques, DL-based object detection techniques have been extensively applied in aquaculture with the advantage of simultaneously classifying and localizing fish of interest in images. This study reviews the relevant research status of DL-based object detection techniques in fish counting, body length measurement, and individual behavior analysis in aquaculture. The research status is summarized from two aspects: image and video analysis. Moreover, the relevant technical details of DL-based object detection techniques applied to aquaculture are also summarized, including the dataset, image preprocessing methods, typical DL-based object detection algorithms, and evaluation metrics. Finally, the challenges and potential trends of DL-based object detection techniques in aquaculture are concluded and discussed. The review shows that generic DL-based object detection architectures have played important roles in aquaculture.

Production and identification of dipeptidyl peptidase IV (DPP-IV) inhibitory peptides from discarded cowhide collagen - Long He; Xinyue Wang; Yanru Wang; Jin Luo; Yining Zhao; Guangxing Han; Ling Han; Qunli Yu (Food Chemistry, 2023)

Integrated waterproofing evaluation method for longitudinal joints of shield tunnel subjected to extreme surcharge: Numerical analysis and experimental validation - Qing Ai; Yining Gu; Yong Yuan; Xiaomo Jiang; Hui Wang; Haitao Yu; Yongjie Huang (Tunnelling and Underground Space Technology, 2023)

Tailoring mixed geometrical configurations in amorphous catalysts to activate oxygen electrode reactions of lithium-oxygen batteries - Runjing Li; Anjun Hu; Chuan Zhao; Bo Zhou; Miao He; Yining Fan; Jiahao Chen; Zhongfu Yan; Yu Pan; Jianping Long (Chemical Engineering Journal, 2023)

Combination of Polyethylene Glycol-Conjugated Urokinase Nanogels and Urokinase for Acute Ischemic Stroke Therapeutic Implications - Ding Nan; Haiqiang Jin; Di Yang; Weiwei Yu; Jingjing Jia; Zemou Yu; Hui Tan; Yongan Sun; Hongjun Hao; Xiaozhong Qu; Yining Huang (Translational Stroke Research, 2021)

The role of exosomal microRNAs in central nervous system diseases - Yifei Yu; Kun Hou; Tong Ji; Xishu Wang; Yining Liu; Yangyang Zheng; Jinying Xu; Yi Hou; Guangfan Chi (Molecular and Cellular Biochemistry, 2021)

New insights into targeting mitochondria in ischemic injury - Jingjing Jia; Haiqiang Jin; Ding Nan; Weiwei Yu; Yining Huang (Apoptosis, 2021)

2’-Fluoro-2’-deoxycytidine inhibits murine norovirus replication and synergizes MPA, ribavirin and T705 - Peifa Yu; Yining Wang; Yunlong Li; Yang Li; Zhijiang Miao; Maikel P. Peppelenbosch; Qiuwei Pan (Archives of Virology, 2020)
Noroviruses are the main causative agents of acute viral gastroenteritis worldwide. However, no vaccine or specific antiviral treatment is available, imposing a heavy global health burden. The nucleoside analogue 2’-fluoro-2’-deoxycytidine (2’-FdC) has been reported to have broad antiviral activity. Here, we report that 2’-FdC significantly inhibits murine norovirus replication in macrophages. This effect was partially reversed by exogenous supplementation of cytidine triphosphate. The combination of 2’-FdC with mycophenolic acid, ribavirin or favipiravir (T705) exerts synergistic antiviral effects. These results indicate that 2’-FdC is a potential candidate for antiviral drug development against norovirus infection.

DNA damage response manages cell cycle restriction of senile multipotent mesenchymal stromal cells - Lin Yao; Fanyuan Yu; Yining Xu; Yitian Wang; Yanqin Zuo; Chenglin Wang; Ling Ye (Molecular Biology Reports, 2020)

Environmentally persistent free radicals in PM2.5: a review - Mengxia Xu; Tao Wu; Yu-Ting Tang; Tong Chen; Lavrent Khachatryan; Poornima Ramesh Iyer; Dengting Guo; Anran Chen; Miao Lyu; Jinhu Li; Jiaqi Liu; Dan Li; et al. (Waste Disposal & Sustainable Energy, 2019)

Spatial and temporal evolution of landfast ice near Zhongshan Station, East Antarctica, over an annual cycle in 2011/2012 - Jiechen Zhao; Qinghua Yang; Bin Cheng; Matti Leppäranta; Fengming Hui; Surui Xie; Meng Chen; Yining Yu; Zhongxiang Tian; Ming Li; Lin Zhang (Acta Oceanologica Sinica, 2019)

The Concept of Ecthyma Gangrenosum Illustrated by a Fusarium oxysporum Infection in an Immunocompetent Individual - Yanping Jiang; Abdullah M. S. Al-Hatmi; Yining Xiang; Yu Cao; Albert H. G. Gerrits van den Ende; Ilse Curfs-Breuker; Jacques F. Meis; Hongguang Lu; G. Sybren de Hoog (Mycopathologia, 2016)

Imaging Lignin-Downregulated Alfalfa Using Coherent Anti-Stokes Raman Scattering Microscopy - Yining Zeng; Brian G. Saar; Marcel G. Friedrich; Fang Chen; Yu-San Liu; Richard A. Dixon; Michael E. Himmel; X. Sunney Xie; Shi-You Ding (BioEnergy Research, 2010)